Insomnia and emotion regulation - Vanek, Jakub; Prasko, Jan; Genzor, Samuel; Ociskova, Maria; Holubova, Michaela; Sova, Milan; Kantor, Krystof; Slepecky, Milos; Nesnidal, Vlastimil (Neuro-endocrinology letters, 2020)
OBJECTIVE: Insomnia and affective disorders are among the most common and disabling health problems of our society. Although there seems to be a clear link between poor sleep and problems in emotional regulation, it is still an area with many remaining questions. While the cognitive and behavioural consequences of poor sleep and insomnia have been studied in depth in recent decades, emotional experience empirical findings in this area still need to be replicated and confirmed. METHOD: Review article included studies published from January 1990 to March 2020 accessed via PubMed database. The keywords "Insomnia, Emotional regulation, Nightmares, Mental disorders, Sleep quality, Nightmares treatment" were used in various combinations. The total of 145 articles was found, and after their complete review, 42 papers were selected. Secondary texts from reference lists of primarily selected articles were examined and added to the primary document list. Finally, a total of 159 articles were included in the review. RESULTS: Sleep is involved in emotion regulation both in the general population and individuals with various mental disorders. Several studies found that pre-sleep emotional activation of negative and positive emotions disturbs sleep by enhancing emotional excitement. On the other hand, many studies showed that poor sleep quality and sleep deprivation adversely affects the emotional functioning in adults. The results of the studies summarized in this review show that emotional regulation can mediate the effect of insomnia on various psychiatric disorders. Insomnia can be a significant risk factor that should be targeted in various psychiatric disorders. CONCLUSION: Targeted prevention of affective disorders in patients who have insomnia, as well as identification of transformation mechanisms, could be an advantageous approach to alleviating their burden. Complex treatment, including cognitive-behavioural therapy for insomnia, added to the primary treatment of these disorders, is recommended.
Keywords: Emotions; Humans; spánek REM; poruchy iniciace a udržování spánku; Emotional Regulation; Cognitive Behavioral Therapy; emoční regulace; lidé; Sleep, REM; Sleep; emoce; kognitivně behaviorální terapie; Sleep Initiation and Maintenance Disorders; spánek